Aplikasi Terintegrasi Registrasi Torche Education Menggunakan Framework Django - Regi Apriandi; Bita Parga Zen (Politeknik Negeri Cilacap, 2022)
The growth of frameworks for web application development is very rapid, especially on the back side (server) of web development or what is commonly called the backend. Several programming languages ​​offer frameworks that have their own advantages, such as the Python programming language which offers a web application development framework, namely Django. It is equipped with the fast development, fast processing, and scalability. The data collection process was carried out by researching several related sources regarding the modules in the Django framework. The research process was carried out by finding sources of information about the Django framework to support the design of the Torche Education class registration application. Sources of information are collected to become a reference for application development. The Torche Education class registration application was built during the internship process at the company as it is concerned with developing the application according to predetermined working hours. It started by conducting research on the modules in the Django framework for developing registration applications and then followed by implementing the framework and integrating the application into several platforms such as Google Drive, Discord, and Gmail. Based on the application development above, the backend framework technology has been implemented in Python programming, namely Django. The results and benefits of the research can be useful for facilitating related parties in the process of recruiting students for class registration and making it easier for users to get fast information.